Trabalho e linguagem na obra de A. R. Luria: um estudo à luz da ontologia marxiana. - Silva, Natália Ayres (2011)
This dissertation, which has a bibliographical nature, was centered upon the analysis of the categories of labor and language in the work of Alexander Romanovich Luria. From the point of view of Marxian-Lukacsian ontology, it assumed labor as the act that founded human world and all the complexes which encompass human experience. Therefore, it elected as the main hypothesis, that labor, as the founding category of the social being, with the special participation of language, accounts for the origin of the conscientious activity and of the higher psychological functions in humans, both resulting from the necessities engendered by human activity itself. In this perspective, we tried to investigate to what extent the treatment ascribed by Luria to the categories of labor and language are consistent with the premises put by the ontology of social being, identifying, moreover, their relationship within the genesis and development of the higher psychological functions. Before discussing the main research questions, we considered of great importance to present Luria’s biography, in order to place the historical context in which his ideas were fostered, attesting his affiliation with Vigotski and Leontiev, as well, in the field of historical-dialectical materialism. The results of the research indicated that the treatment given by Luria to the categories of labor and language agree with the fundamental ontological concepts, emphasizing labor as the primary category in relation to the other complexes, herein included the complex of language. In this context, labor, together with language, brought about human conscientious activity, developing in man, complex functions, which are not present in animals.